Estudo da resistência à corrosão de superfícies metálicas recobertas com revestimento à base de lignina - Diógenes, Otílio Braulio Freire (2019)
Commercial varnishes used inside metal packaging for food preservation contain in their chemical formulation the compound Bisphenol A (BPA). During the manufacturing process of the packages, especially in the sterilization step, it is possible that migration of the BPA from the coating to the canned food occurs, causing human exposure to the compound. Studies have shown that BPA acts as an endocrine disruptor in the body. Therefore, finding an alternative material to BPA for the synthesis of organic coatings becomes necessary. This work aims to develop organic protective coatings against corrosion and free of BPA for substitutive application to commercial varnishes. The coatings were produced by mixing hydroalcoholic solution of edible gelatine with different concentrations of alkaline lignin. Samples of tinned steel (tinplate) and aluminium, with dimensions of 50 mm x 50 mm x 0.19 mm and 50 mm x 50 mm x 0.5 mm, respectively, were used as substrates. Test specimens were coated with commercial varnish for comparison. Lignin and coatings were characterized by Fourier Transform Infrared Spectroscopy (FTIR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) techniques. The corrosion behaviour of the coatings was performed by electrochemical tests of open circuit potential and electrochemical impedance spectroscopy (EIS). A 0.154 mol/L NaCl solution was used as the electrolyte at room temperature. The tensile strength of the coatings was studied by the tensile test according to ASTM D882. EIS results indicated an improvement in the corrosion protection of the metal substrates with increasing lignin concentration in the coating.